2018
DOI: 10.1002/marc.201800191
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting NH···Cl Hydrogen Bonding Interactions in Cooperative Metallosupramolecular Polymerization

Abstract: The self-assembly features of hydrophobic bispyridyldichlorido Pd(II) complexes, equipped with an extended aromatic surface derived from oligophenyleneethynylene (OPE) and polarizable amide functional groups, are reported. The cooperative supramolecular polymerization of these complexes results in bundles of thin fibers in which the monomer units are arranged in a translationally displaced or slipped fashion. Spectroscopic and microscopy studies reveal that these assemblies are held together by simultaneous π-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…The chirality of 1 is confirmed due to the C1 and C6 atoms and verified by the space group and Flack parameter. The primary (N1) and secondary (N2) amines of L1 are experienced in the hydrogen bondings with Cl atoms of neighboring zinc(II) complexes: N1•••Cl1′ 3.430 å, ∠N1‐H1A‐Cl1′ 145.00°; N1•••Cl2″ 3.417 å, ∠N1‐H1B‐Cl2″ 170.04°; N2•••Cl2‴ 3.418 å, ∠N2‐H2‐Cl2″ 165.38° (′=− x + 1, y − 0.5, −z + 2; ″= − x + 1, y + 0.5, −z + 2; ‴ = x, y + 1, z) . Thus, 1 shows one‐dimensional hydrogen bonding structure along the b axis (Figure 4a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chirality of 1 is confirmed due to the C1 and C6 atoms and verified by the space group and Flack parameter. The primary (N1) and secondary (N2) amines of L1 are experienced in the hydrogen bondings with Cl atoms of neighboring zinc(II) complexes: N1•••Cl1′ 3.430 å, ∠N1‐H1A‐Cl1′ 145.00°; N1•••Cl2″ 3.417 å, ∠N1‐H1B‐Cl2″ 170.04°; N2•••Cl2‴ 3.418 å, ∠N2‐H2‐Cl2″ 165.38° (′=− x + 1, y − 0.5, −z + 2; ″= − x + 1, y + 0.5, −z + 2; ‴ = x, y + 1, z) . Thus, 1 shows one‐dimensional hydrogen bonding structure along the b axis (Figure 4a).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, in the molecular structure of 2 , the zinc(II) ion displays tetrahedral geometry, coordinated with one primary amine of L2 with the ZnN1 distance of 2.046 (2) å and one secondary amine of L2 with the ZnN2 distance of 2.098 (2) å as well as two chloride ions with the average ZnCl distance of 2.224 (1) å (Figure ) . The primary (N1) amine of L2 is experienced in the hydrogen bondings with Cl atoms of neighboring zinc(II) complexes: N1•••Cl1 ’ 3.502 å, ∠N1‐H1A‐Cl1 ′ 175.26°; N1•••Cl2 ″ 3.317 å, ∠N1‐H1B‐Cl2 ″ 157.30° ( ′= − x + 2, y − 0.5, −z + 1; ″ = − x + 2, y + 0.5, −z + 1) . Thus, 2 exhibits one‐dimensional hydrogen bonding structure along the b axis (Figure b).…”
Section: Methodsmentioning
confidence: 99%
“…[34][35][36][37] Preliminary self-assembly studies of the (S)-enantiomer of Pd complex 1, however, suggested the presence of a single supramolecular species if monomer solutions in methylcyclohexane (MCH) were cooled from 363 K to 283 K at a rate of 1 K min À1 . 28 Herein, we re-investigated in detail the supramolecular polymerization of the (R)-enantiomer of 1, using the previously reported (S)-1 as model compound to generalize our ndings. As both enantiomers exhibit an identical behaviour (except for the opposite sign of the CD signals, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a), the (S)isomer of which was suggested in our preliminary work to form a single aggregate species. 28 By doing so, we discovered a hidden, kinetic, cooperative state that is not accessible in its pure form by means of thermally controlled supramolecular polymerization, due to a lower T e than the thermodynamic species. The hidden pathway incorporates two consecutive species, Agg II and its rapidly forming superstructures (Agg IIc, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Metal triggered-supramolecular gels based on the metal–ligand complex have also attracted much attention as a significant class of organic/inorganic hybrid supramolecular materials [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Due to the combination of metal complexes in metal triggered-supramolecular gels, these metal-containing systems exhibit redox, optical, electrochromic, catalytic, and magnetic properties [ 22 , 23 , 24 , 25 , 26 ]. In particular, chiral metal triggered-supramolecular gels are attractive because they are applicable to chiral recognition and sensing, and asymmetric catalysis [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%